EFEKTIVITAS PEMBERIAN BUAH PISANG AMBON DAN JUS BUAH SEMANGKA TERHADAP PENURUNAN TEKANAN DARAH PENDERITA HIPERTENSI PADA LANSIA DI RW 02 KEBON DUREN KALIMULYA KOTA DEPOK JAWA BARAT TAHUN 2025 - Wiwin Sukarni; Indri Sarwili; Nurul Ainul Shifa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Background: Hypertension is one of the various degenerative diseases that we often encounter in the elderly. Objective: This study was to determine the differences in effectiveness of giving Ambon bananas and watermelon juice to lower blood pressure in elderly hypertension sufferers. Method: Quasy experiment with Two group design, pretest- posttest design. The sampling technique used purposive sampling in this study, the number of samples was 30. The instruments in this study used a sphygmomanometer, stethoscope and respondent observation sheet. Results: The results of the study using the Wilcoxon test and the difference test for the two interventions using the Mann-Whitney test obtained the results of the analysis of Ambon bananas with a systolic p-value of 0.000, where p <α 0.05 and a diastolic p-value of 0.001, where p <α 0.05, meaning that there is an effect of giving Ambon bananas to reduce high blood pressure in elderly people with hypertension. For the results of watermelon juice, the systolic p-value was 0.001, where p < α 0.05 and the diastolic p-value pressure in elderly people with hypertension. For the results of watermelon juice, the systolic p-value was 0.001, where p < α 0.05 and the diastolic p-value reduce high blood pressure in elderly people with hypertension. The results of the Mann-Whitney test analysis obtained a significant systolic p-value of 0.008, where p <α 0.05 and a diastolic p-value of 0.051 p <α 0.05, meaning that there is a difference in the effectiveness of giving Ambon bananas and watermelon juice to lower blood pressure in elderly people with hypertension in RW 02 Kebon Duren Kalimulya, Depok City. Conclusion: Ambon bananas contain high levels of potassium, while watermelon juice contains beta-carotene and potassium, which can lower blood pressure without side effects